2018
DOI: 10.4012/dmj.2017-334
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the wettability of different titanium surface topographies on initial cellular behavior

Abstract: This study examined the influence of the time-dependent wettability of different surface topographies on initial cellular behavior. Titanium disks with smooth topography (SM) and three kinds of rough topography (sandblasted (SA), microtopography (M) and nanotopography (N)) were prepared. Time-dependent changes in surface wettability were observed in all surfaces as shown in previous studies. On SM surfaces, hydrophobic alteration influenced cell spreading and the activity of RhoA (a small GTPase protein of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The contact angle determines the wettability of materials. In general, a hydrophilic surface results in a better osteogenic ability than a hydrophobic surface [ 22 ]. In the present study, the average contact angle of SLA-titanium was 101.8°, which indicates that SLA-titanium can be considered hydrophobic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle determines the wettability of materials. In general, a hydrophilic surface results in a better osteogenic ability than a hydrophobic surface [ 22 ]. In the present study, the average contact angle of SLA-titanium was 101.8°, which indicates that SLA-titanium can be considered hydrophobic.…”
Section: Discussionmentioning
confidence: 99%
“…The ALP activity at 7 days was negatively correlated with the surface roughness (S a , R a ) and contact angle. Nishimura et al reported that a hydrophilic surface was more advantageous to initial cell attachment than a hydrophobic surface [ 22 ]. It is therefore reasonable that SLA-titanium showed lower ALP activity at 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…A pure titanium surface will form an oxidized layer immediately following exposure to air, which is quite stable [21]. It has been shown that multiple types of cells can proliferate and adhere to pure titanium [22,23,24,25]. Therefore, pure titanium, with its excellent biocompatibility and corrosion resistance, has been widely used as a biocompatible material for more than half a century [13].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts interact with the substrates via integrins, which cluster and associate with cytoskeletal elements forming focal adhesions, and the rough and hydrophilic surface of the biomaterials could augment the density of focal adhesions . As a result of the extracellular cues, the more numerous focal adhesions present on the substrates increase cell complexity and enable the formation of filopodia-like structures, through the cytoskeleton arrangement .…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts interact with the substrates via integrins, which cluster and associate with cytoskeletal elements forming focal adhesions, and the rough and hydrophilic surface of the biomaterials could augment the density of focal adhesions. 36 As a result of the extracellular cues, the more numerous focal adhesions present on the substrates increase cell complexity and enable the formation of filopodia-like structures, through the cytoskeleton arrangement. 37 In this study, the cells adhesion and spreading on the samples were improved with the increase of SN content in the microporous coatings, demonstrating that SN played important roles in promoting cell adhesion and spreading.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%